The influence of pigmentation of moor frog (Rana arvalis) to the sizes of pinworms with the different locations (Experimental biology, 2015)
Nematodes with the location in the digestive tract (Oswaldocruzia filiformis) reached the maximal sizes usually in fair frogs, minimal sizes – always in the frogs with intensive pigmentation. In 2008-2009 years with relatively low quantity of Rhabdias bufonis these nematodes reached the maximal sizes in fair frogs, but in 2010 year, with comparable rising of infective indicators, - in the dark amphibians (with the minimal sizes in fair-colour hosts). It is probably, that small quantity of the blood-feeding nematode (which is more energetic expensed for the frogs’ organism in comparison of gastrointestinal parasites) leaded to the minimal sizes in fair-colour hosts with their more economic metabolism, whereas in the case of the increasing of infection intensity the semi-populations of helminthes in the dark amphibians – with more intensive metabolism and, consequently, possibility of quick restoration of energetic expenditure from the blood-feeding of parasites – got the advantages.
Keywords: helminthes hemipopulation; fair frog; nematodes; Oswaldocruzia filiformis